Isokinetic leg strength profile of elite male basketball players - Bradic, A.; Bradic, J.; Pasalic, E.; Markovic, G. (The Journal of Strength and Conditioning Research, 2009)
In this study, we described the leg strength profile of elite male basketball players and evaluated the positional differences in absolute and relative leg strength. Forty-three elite male basketball players (15 guards, 14 forwards, and 14 centers) performed maximal isokinetic concentric knee extension and flexion efforts (60°/s and 180°/s) and ankle plantar flexion and dorsiflexion efforts (30°/s and 60°/s). Significant (p < 0.01) positional differences in absolute leg muscle strength were observed, with centers having significantly (p < 0.05) greater peak torques compared with guards in all of the tested muscle groups and at all angular velocities. Moreover, centers also possessed significantly (p < 0.05) stronger plantar flexors at 30°/s and dorsiflexors at 60°/s compared with forwards, and forwards possessed significantly (p < 0.05) stronger knee extensors, plantar flexors, and dorsiflexors compared with guards. Normalization of strength values with body mass (N·m/(kg)) canceled out the positional differences in knee extensor and flexors strength, but the groups still differed significantly (p < 0.01) in relative plantar flexion and dorsiflexion strength. Specifically, centers had significantly (p < 0.05) stronger plantar flexors and dorsiflexors at both angular velocities compared with guards, as well as significantly (p < 0.05) stronger plantar flexors at 30°/s and dorsiflexors at 60°/s compared with forwards. Our results suggest that the positional differences in quadriceps and hamstring muscle strength of elite male basketball players are the result of respective differences in body size, whereas factors other than body size are responsible for the positional differences in ankle plantar flexor and dorsiflexor strength. These results together with the presented normative isokinetic leg strength data can be useful for coaches and therapists when designing and evaluating position-specific strength training and rehabilitation programs of elite male basketball players.